2014
DOI: 10.1074/jbc.m114.571182
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Regulatory Factor 8 (IRF8) Interacts with the B Cell Lymphoma 6 (BCL6) Corepressor BCOR

Abstract: Background: Protein partnerships regulate specific functions of cells. BCOR protein-protein interactions are critical to aspects of B cell biology. Results: IRF8 pairs with BCOR in the nucleus to enhance its transcriptional repressive activity. Conclusion: Partnering of IRF8 with BCOR defines a novel mechanism for controlling B cell gene expression. Significance: Understanding gene regulation in specific cell types requires identification of protein complexes that modulate expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…This is in accord with concepts elaborated by Hodgkin and colleagues based on in vitro data, including recent elegant single-cell studies of short-term B cell cultures (Duffy et al, 2012). In this regard, mRNAs encoding several key transcription factors and co-factors related to GC, MBC and LLPC identity are differentially expressed in early and late GCBC, including Irf8, Egr1, Mef2b, Sh3bgrl2 (whose protein is an interacting partner with Irf8 (Yoon et al, 2014), and Zbtb20 (also known as Zfp288 ), which has been recently implicated in the development of LLPC (Chevrier and Corcoran, 2014; Nutt et al, 2015; Wang and Bhattacharya, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…This is in accord with concepts elaborated by Hodgkin and colleagues based on in vitro data, including recent elegant single-cell studies of short-term B cell cultures (Duffy et al, 2012). In this regard, mRNAs encoding several key transcription factors and co-factors related to GC, MBC and LLPC identity are differentially expressed in early and late GCBC, including Irf8, Egr1, Mef2b, Sh3bgrl2 (whose protein is an interacting partner with Irf8 (Yoon et al, 2014), and Zbtb20 (also known as Zfp288 ), which has been recently implicated in the development of LLPC (Chevrier and Corcoran, 2014; Nutt et al, 2015; Wang and Bhattacharya, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that IRF8 is one of the key players in regulating B-cell development and functions 14 , 15 , 25 , 26 . However, IRF8's role in the development of B-cell malignancies remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…For lymphoid lineage, IRF8 was critical in controlling early stage B cell development as well as marginal zone and follicular B-cell development 13 , 14 . IRF8 positively regulated BCL6, a transcription factor critical for the development and function of germinal center B cells, through direct and indirect actions 15 . Mice deficient in Irf8 had impaired germinal center (GC) formation 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Their new functional roles are constantly being discovered [3]. Importantly, many of these interactions are implicated in human diseases such as cancer or autoimmune disease [4][5][6][7]. Therefore, structure-based studies directed toward the design of completely new or modified receptor-interacting peptides have become a hot spot of current biomedical research.…”
Section: Introductionmentioning
confidence: 99%